Un vertedero tardío en Cartagena, c/. Duque, 33 - Laiz Reverte, Mª Dolores; Berrocal Caparrós, Mª del Carmen (Antigüedad y Cristianismo, 1991)
This is a study of a rubbish dump discovered during the exacavation of a house dated to the Augustean period in the Calle del Duque, 33, Cartagena. This dump is located in the outskirts of a late ancient city and contains ceramics dated to the second half of the sixth century and the beginning of the seventh.